2018
DOI: 10.1002/adfm.201707406
|View full text |Cite
|
Sign up to set email alerts
|

DNA Computing Boosted by a Cationic Copolymer

Abstract: This article is protected by copyright. All rights reserved. 2The huge information storage capability of DNA and its ability to self-assemble can be harnessed to enable massively parallel computing in a small space. DNA-based logic gates have been designed that rely on DNA strand displacement reactions; however, computation is slow due to timeconsuming DNA reassembly processes and prone to failure as DNA is susceptible to degradation by nucleases and under certain solution conditions. Here we show that the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Additionally, circuits immobilized on static scaffolds are sensitive to assembly defects as non- or mis-incorporated reactants will terminate the propagation of the signal along the scaffold. ,, Because the probability of assembly defects increases with the circuit’s complexity, the scalability of immobilized circuits therefore remains challenging. Other efforts to increase the kinetics of DNA strand displacement include the use of RecA as a protein-based catalyst and the use of cationic copolymers, which are postulated to enhance kinetics by stabilizing toehold complex formation. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, circuits immobilized on static scaffolds are sensitive to assembly defects as non- or mis-incorporated reactants will terminate the propagation of the signal along the scaffold. ,, Because the probability of assembly defects increases with the circuit’s complexity, the scalability of immobilized circuits therefore remains challenging. Other efforts to increase the kinetics of DNA strand displacement include the use of RecA as a protein-based catalyst and the use of cationic copolymers, which are postulated to enhance kinetics by stabilizing toehold complex formation. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, to realize the same goal, Maruyama's group showed that a cationic copolymer, poly(llysine)-graft-dextran (PLL-g-Dex), can also elevate the speed of DNA logic operations. [99] This work reduced the operating time from hours-level to minutes-level and also strengthened the nuclease resistance ability of DNA circuits. Although above works evidently improved the computing speed, the used polymers usually need complicated synthesis and purification procedure, this is one problem that needs to be taken seriously in the future.…”
Section: Polymersmentioning
confidence: 92%
“…To realize chemical AI, dependable design methods for recursive DNA circuits must be established, and a variety of new functional molecules must be developed. Cationic copolymers, [ 49 ] which dramatically increase the reaction rate of DNA‐strand displacement, are one such type of functional molecule.…”
Section: Principle Of Learning In Dna Circuitsmentioning
confidence: 99%